2011
DOI: 10.1002/ieam.219
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the future decline of wild coho salmon populations resulting from early spawner die-offs in urbanizing watersheds of the Pacific Northwest, USA

Abstract: Since the late 1990 s, monitoring efforts evaluating the effectiveness of urban stream restoration projects in the greater metropolitan area of Seattle, Washington, USA, have detected high rates of premature mortality among adult coho salmon (Oncorhynchus kisutch) in restored spawning habitats. Affected animals display a consistent suite of symptoms (e.g., disorientation, lethargy, loss of equilibrium, gaping, fin splaying) that ultimately progresses to death on a timescale of a few hours. Annual rates of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…Recent population-scale modeling has shown the potential for rapid local declines in coho population abundance across the range of spawner mortality rates observed in urban drainages during the course of this study [29]. Regional human population growth and land use changes that increase the proportion of impervious surfaces within watersheds may therefore pose an important future threat to wild coho populations if 1) toxic urban runoff is the underlying cause of the mortality phenomenon, and 2) wild coho are similar in their vulnerability to the hatchery and unmarked (and presumably wild) coho that were found unspawned in 2002–2009.…”
Section: Discussionmentioning
confidence: 98%
“…Recent population-scale modeling has shown the potential for rapid local declines in coho population abundance across the range of spawner mortality rates observed in urban drainages during the course of this study [29]. Regional human population growth and land use changes that increase the proportion of impervious surfaces within watersheds may therefore pose an important future threat to wild coho populations if 1) toxic urban runoff is the underlying cause of the mortality phenomenon, and 2) wild coho are similar in their vulnerability to the hatchery and unmarked (and presumably wild) coho that were found unspawned in 2002–2009.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, natural production of coho in Seattle-area urban streams is very low. Not unexpectedly, recent modeling has shown that local coho population abundance declines precipitously at rates of spawner mortality documented for these drainages [11]. The adult returns to these streams are thus likely to be animals straying into sink or attractive nuisance habitats.…”
Section: Methodsmentioning
confidence: 96%
“…Spromberg and Scholz 48 modeled the impact of prespawn mortality and dispersal rates of coho salmon ( Oncorhynchus kisutch ) populations in the greater metropolitan area of Seattle, Washington, USA, using a metapopulation model (i.e., a set of populations connected by dispersal of individuals) and varying dispersal rates. Prespawn mortality (PSM) is largely caused by toxic urban storm water runoff.…”
Section: Resistance Resilience and Recovery From Disturbancesmentioning
confidence: 99%